Approaching the Roman revolution papers on Republican history - Syme, Ronald 1903-1989 (Oxford University Press, 2016)
This volume collects 26 studies on Republican history by the late Sir Ronald Syme (1903-1989), drawn from the archive of his papers at the Bodleian Library. They shed light on aspects of Republican history that were either overlooked or tangentially discussed in Syme's published work. Taken as a whole, they enable us to reach a more comprehensive assessment of his intellectual and historiographical profile
Keywords: Geschichte 510 v. Chr.-27 v. Chr.; Geschichte; Rom; Rome / History / Republic, 510-30 B.C.; Rome / History / Augustus, 30 B.C.-14 A.D.; Römisches Reich